Protocol for the intake assessments performed in the context of the revision of Tolerable Upper Intake Levels for selected nutrients. Issue 8 (18th August 2022) - ,; de Sesmaisons Lecarré, Agnès; Fabiani, Lucia; de Sousa, Rita Ferreira; Horvath, Zsuzsanna
Abstract: Upon request of the European Commission, EFSA is requested to update the Tolerable Upper Intake Levels (ULs) for folic acid/folate, iron, selenium, manganese, vitamin A, vitamin B6, vitamin D, vitamin E and β‐carotene. According to the EFSA NDA Panel draft guidance for establishing and applying ULs for vitamins and minerals, the risk assessment foresees an intake assessment step to inform the risk characterisation. This protocol describes the methodologies that will be used to assess the intake of these micronutrients in EU populations, based on the data available in the EFSA Comprehensive Food Consumption Database and the EFSA Food Composition Database. Complementary sources of information, in particular regarding intakes of nutrient resulting from their addition to foods ('fortified foods') and their used in food supplements, are identified. This document outlines the generic approach applied to all nutrients. Where necessary it will be complemented to address the specificities of individual nutrients.